Reward-Related Dysfunctions in Children Developing Attention Deficit Hyperactivity Disorder—Roles of Oppositional and Callous-Unemotional Symptoms - Schloß, Susan; Derz, Friederike; Schurek, Pia; Cosan, Alisa Susann; Becker, Katja; Pauli-Pott, Ursula (Frontiers in Psychiatry, 2021)
Objectives. Neurocognitive functions might indicate specific pathways in developing attention deficit hyperactivity disorder (ADHD). We focus on reward-related dysfunc¬tions and analyze whether reward-related inhibitory control (RRIC), approach motiva¬tion, and autonomic reactivity to reward-related stimuli are linked to developing ADHD, while accounting for comorbid symptoms of oppositional defiant disorder (ODD), and callous-unemotional (CU) traits. Methods. A sample of 198 preschool children (115 boys; age: m=58, s=6 months) was re-assessed at age 8 years (m=101.4, s=3.6 months). ADHD diagnosis was made by clinical interviews. We measured ODD symptoms and CU traits using a multi-informant approach, RRIC and approach tendency using neuro¬psychological tasks, and autonomic reactivity via indices of electro¬dermal activity (EDA). Results. Low RRIC and low autonomic reactivity were uniquely associated with ADHD, while longitudinal and cross-sectional links between approach motivation and ADHD were completely explained by comorbid ODD and CU symptoms. Conclusion. High approach motivation indicated developing ADHD with ODD and CU problems, while low RRIC and low reward-related autonomic reactivity were linked to developing pure ADHD. The results are in line with models on neurocognitive sub¬types in externalizing disorders.